Biocompatibility of NiTi alloy implants in vivo - Tosun, Gul; Unsaldi, Emine; Ozler, Latif; Orhan, Nuri; Durmus, Ali Said; Eroksuz, Hatice (Elsevier Sci Ltd, 2013)
[Abstract Not Available]
European Biotechnology Congress -- MAY 16-18, 2013 -- Comenius Univ, Bratislava, SLOVAKIA